The function f(x) = 2x - 3

f(x + 1) = 2(x + 1) - 3

=> 2x + 2 -3

=> 2x - 1

f(x - 1) = 2(x - 1) - 3

=> 2x - 2 - 3

=> 2x - 5

g(x) = f(x + 1) +...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function f(x) = 2x - 3

f(x + 1) = 2(x + 1) - 3

=> 2x + 2 -3

=> 2x - 1

f(x - 1) = 2(x - 1) - 3

=> 2x - 2 - 3

=> 2x - 5

g(x) = f(x + 1) + f(x - 1)

=> 2x -1 + 2x - 5

=> 4x - 6

**The required function g(x) = 4x - 6**